Distinct evolutionary histories of lowland biota on Italian and Balkan peninsulas revealed by the phylogeography of Arundo plinii (Poaceae). (30th June 2014) - Hardion, Laurent; Baumel, Alex; Verlaque, Régine; Vila, Bruno; Linder, Peter
Abstract Aim Although recognized as hotspots of biodiversity, Mediterranean peninsulas have been poorly studied with regard to the evolutionary legacy of Quaternary environmental changes for endemic lowland biota. Using the phylogeography of the lowland Arundo plinii Turra (Poaceae), we evaluated two hypotheses regarding the genetic structure of southern European species, that there is: (H1) a decrease in regional genetic diversity with increasing latitude induced by past contractions towards southern refugia; and (H2) a strong differentiation between isolated refugia without a latitudinal gradient in genetic diversity. Location Italian and Balkan peninsulas, Mediterranean Basin. Methods Arundo plinii from 59 localities across six geographical areas was analysed for three genetic markers: (1) five intergenic spacers (4590 bp) of plastid DNA, investigated by molecular dating and phylogeographical analyses; (2) six primer pairs (852 fragments) of amplified fragment length polymorphism (AFLP) fingerprinting, analysed as indices of genetic structure and diversity; and (3) chromosome counts regarding the prevalence of polyploidy in the genus Arundo. Results Chloroplast DNA and AFLP both described a gradient of genetic diversity in Italy, from the highest values in Sicily to uniform genetic clusters in northern Italy, versus relatively high genetic diversities in both northern and southern parts of the Balkans. Moreover, they supported a strong genetic differentiation between the two peninsulas, despite the distinction of one admixed genotype located in Croatia. Polyploid events were detected in northern and southern margins of the species' distribution. Main conclusions The results support distinct Pleistocene evolutionary histories for A. plinii within the two peninsulas. In Italy, this species probably persisted mainly in southern regions (Calabria and Sicily) during the Pleistocene glaciations, leading to the more recent formation of the northern populations. Conversely, the Balkan populations probably persisted at different latitudes during the Pleistocene, as illustrated by the conservation of equivalent genetic diversities in both the northern and southern Balkans.